2011
DOI: 10.1177/1553350611415425
|View full text |Cite
|
Sign up to set email alerts
|

Single-Incision Laparoscopic Reversal of Hartmann Procedure via the Colostomy Site Only

Abstract: SILS Hartmann procedure reversal via the colostomy site is safe. The approach avoids additional incisions and allows avoidance of dense adhesions to the previous midline incision--a new benefit of SILS, apart from cosmesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…A review of the literature reveals that only a few small case series have been published on this technique. At the moment no randomized controlled trials were published [37][38][39][40][41][42]. Table 5 summarizes the results of the available literature.…”
Section: Appraisal Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature reveals that only a few small case series have been published on this technique. At the moment no randomized controlled trials were published [37][38][39][40][41][42]. Table 5 summarizes the results of the available literature.…”
Section: Appraisal Of the Literaturementioning
confidence: 99%
“…Table 5 summarizes the results of the available literature. The technique was first described by Smith and colleagues [42]; in this case single-port restoration of the intestinal continuity was performed in a 56-year-old patient with a history of perforated diverticulosis. Their total operation time was 104 min.…”
Section: Appraisal Of the Literaturementioning
confidence: 99%
“…Conventional multiport laparoscopic (CL) RoH appears to have less morbidity than open surgery (OS) RoH [10][11][12][13], although there is a paucity of randomized data. The technique of single-incision laparoscopic (SIL) RoH through the stoma site was first reported in 2011 [14][15][16]. There was an obvious cosmetic benefit with favourable results in terms of short-term morbidity and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, utilization of the colostomy site for laparoscopic reversal of Hartmann' s procedure was introduced, and several studies have shown the feasibility of the procedure. [1][2][3][4][5] It allows for the colostomy site as an access port for the operation. However, single port surgery is technically more challenging than multiport surgery due to instrument interference and inaccessible angles from a single site.…”
Section: Introductionmentioning
confidence: 99%